A case report: ovarian apoplexy and ectopic pregnancy at once - Mochammad Imam Santoso; Sutan Chandra (The Indonesian Society of Perinatology, South Jakarta, Indonesia, 2022)
Introduction: Ovarian Apoplexy is the sudden rupture of the ovarium that commonly occurs at the site of the corpus luteum cyst, followed by hemoperitoneum. Extremely uncommon but potentially fatal presentation, hemoperitoneum owing to cyst rupture has just a few cases documented in the literature. We report a woman 6 weeks delaying menstrual period, the pregnancy test was positive (second pregnancy). In this article, we aimed to report a rare case of ectopic pregnancy and ovarian apoplexy. Case Presentation: A 26 Years old woman with a history of abortion in her first pregnancy came to the emergency room with 3 days history of vaginal spotting and mild (2/10) continous right lower abdominal pain. She was suspected of incomplete abortion from primary health care. She was in 6 weeks delaying her menstrual period which is an uncommon case for incomplete abortion. The pregnancy test was positive (second pregnancy). Surgery was performed after completing the consent. Upon exploration of the abdomen, approximately 500 MLS of intraabdominal blood was identified. The right ovary's ruptured corpus luteum cyst was discovered to be the cause of the intra-abdominal bleeding. The hemorrhage was simply stopped by electrocauterization. Conclusion: Ovarian Apoplexy concomitantly occurs with an ectopic pregnancy and has not been reported before. Clinical signs and symptoms, especially pain perception of acute abdomen in a person with high pain tolerance, may bias the diagnosis.